Selective endocytic trafficking in live cells with fluorescent naphthoxazoles and their boron complexes1. Issue 44 (4th June 2015) - Dias, Gleiston G.; Rodrigues, Bernardo L.; Resende, Jarbas M.; Calado, Hállen D. R.; de Simone, Carlos A.; Silva, Valter H. C.; Neto, Brenno A. D.; Goulart, Marilia O. F.; Ferreira, Fabricia R.; Meira, Assuero S.; Pessoa, Claudia; Correa, José R.; et al.
<x xml:space="preserve">Abstract</x> Selective probes for endocytic pathway tracking in live cancer cells showed far better selectivity than acridine orange and caveolin-1.